Nonoperative management of hip fractures in very frail elderly patients may lead to a predictable short survival as part of advance care planning. (29th October 2021) - Wijnen, Hugo H; Schmitz, Peter P; Es-Safraouy, Houda; Roovers, Lian A; Taekema, Diana G; Van Susante, Job L C
Abstract : Background and purpose — Surgical treatment is still the mainstay of care even in very frail elderly hip fracture patients. However, one may argue whether surgery is in the best interest of all patients. We elucidated mortality rates of nonoperative management (NOM) of a hip fracture after shared decision-making in a cohort of very frail elderly patients. Patients and methods — Orthogeriatric patients (age > 70 years) admitted with a hip fracture between 2011 and 2019 were included. In the presence of fragility features the motivation for surgery or NOM was supported by advance care planning (ACP) and shared decision-making through geriatric assessment. Mortality rates after NOM were assessed and also presented for the remaining surgical group for reference. Results — In 1, 279 out of 3, 467 patients, geriatric assessment was indicated and subsequently 1, 188 (93%) had surgery versus 91 (7%) NOM. The motivation for NOM was based on patient and family preferences in only 20% of patients, medical grounds in 54%, and a combination of both in 26%. The 30-day and 1-year mortality in the frail NOM group was 87% and 99% respectively, whereas this was 7% and 28% in the surgery group. No statistical comparison between groups was performed due to profound bias by indication. Interpretation — This study provides further insight into the predictable and high short-term mortality after NOM in carefully selected very frail elderly hip fracture patients. This information may help to consider NOM as an alternative treatment option to surgery when no significant gain from surgery is anticipated.